Acute Kidney Injury in Patients Undergoing Chronic Hepatitis C Virus Treatment With Ledipasvir/Sofosbuvir. Issue 10 (24th September 2018) - Brown, Patrick R.; Sadiq, Omar; Weick, Alexander; Lenhart, Adrienne; Elbatta, Mohammad; Fernandez, Christopher; Kutait, Anas; Pompa, Robert; Jafri, Syed‐Mohammed
Abstract : Ledipasvir‐sofosbuvir, a once‐a‐day, oral combination pill, was approved in 2014 for the treatment of chronic hepatitis C infection. Initial trials did not comment on nephrotoxicity; however, recent data suggest a risk of acute kidney injury (AKI) with the use of the medication. We assessed the rates of AKI in patients undergoing ledipasvir‐sofosbuvir in a large, urban tertiary care center. This single‐center retrospective observation study included all patients undergoing therapy from October 1, 2014, to October 1, 2015. Rates of AKI, defined by more than a 0.3 mg/dL increase in serum creatinine level, were calculated. Patients were followed 12 weeks after therapy to assess for sustained viral response as well as to assess for improvement of AKI after completion of therapy, defined by less than 0.2 mg/dL above baseline serum creatinine. In total, 197 patients were included in the final analysis who had completed ledipasvir‐sofosbuvir therapy and completed laboratory values. Among the patients treated, 38 (19%) had AKI during therapy. An additional 4 (2%) had AKI at the end of therapy. Of the 38 patients who experienced AKI, 20 (53%) had improvement in serum creatinine to less than 0.2 mg/dL above their baseline. When comparing for chronic kidney disease (CKD) stage, those with CKD I or II experienced AKI 17% of the time compared with 47% of the time in CKD III or worse ( P = 0.005). Conclusion: AKI was seen in nearly one‐fifth of our patients, and patients with CKD stage III or worse are at increased risk. Although ledipasvir‐sofosbuvir is generally safe in the general population, close monitoring of renal function is recommended. Abstract : Ledipasvir‐sofosbuvir is well transcribed as an effective treatment of chronic hepatitis C virus. Scant literature exists on the possibility of renal toxicity. We describe a 20% incidence of acute kidney failure in patients undergoing ledipasvir‐sofosbuvir therapy and a significantly greater incidence in those with preexisting impaired renal function.